Fashion curating critical practice in the museum and beyond - Vèanskèa, Annamari; Clark, Hazel (Bloomsbury Academic, 2017)
As the practice of fashion curation extends into commercial galleries, public and retail spaces, and even to the individual self, professional concepts of 'curating' are undergoing rapid change. Today, everyone is seemingly able to 'curate', but where does this leave the traditional understanding of curation as clothing collected and displayed in a museum? This thought-provoking volume explores the practice of fashion curating in the 21st century, bridging the gap between methods of display and notions of 'the curatorial' in fashion exhibitions, commercial settings, and the virtual world. From fashion's earliest forays into the museum to creative collaborations between luxury fashion brands and artists, this book challenges understandings of fashion curation by drawing on the palpably new spaces, places, and actors in today's curating scene. Exploring poetic and performative museum displays in venues such as the V&A, Somerset House, MoMu and the Royal Ontario Museum, alongside the ways that brands such as Dior, Chanel and Louis Vuitton have made use of 'the curatorial' in their own commercial strategies, Fashion Curating asks pressing questions about controversial funding and collaboration from the commercial fashion sector, and the limitations of producing exhibitions that are at the same time critical and popular. Bringing together approaches from fashion curators, designers and world-renowned academics, curation is positioned as a critical practice that opens up new ways of conceptualizing and theorizing fashion, challenging how we think and what we already know"-- Provided by publisher